Impact of age on the cumulative risk of transformation in patients with chronic myelomonocytic leukaemia. (1st June 2021) - Machherndl‐Spandl, Sigrid; Jäger, Eva; Barna, Agnes; Gurbisz, Michael; Marschon, Renate; Graf, Temeida; Graf, Elmir; Geissler, Christoph; Hoermann, Gregor; Nösslinger, Thomas; Pfeilstöcker, Michael; Bettelheim, Peter; et al.
Abstract: In older patients with chronic myelomonocytic leukaemia (CMML) and limited life expectancy due to age and or comorbidities, it is particularly important to consider the risk of transformation for individualised treatment decisions. There is limited information on potential differences between younger and older CMML patients regarding the cumulative risk of transformation as well as haematological, molecular and biologic characteristics. We analysed data from the Austrian Biodatabase for CMML (ABCMML) to compare these parameters in 518 CMML patients. Categorisation of patients into 3 age‐related groups: <60 years, 60‐79 years and ≥80 years, showed a significantly lower risk of transformation at higher age by competing risk analysis, with a 4‐year risk of 39%, 23% and 13%, respectively ( P  < .0001). The lower probability of transformation was associated with a lower percentage of blast cells in the peripheral blood (PB) of older patients. Furthermore, we provide a simple score based on age, PB blasts and platelet counts that allowed us to define subgroups of CMML patients with a different cumulative transformation risk, including a low‐risk group with a transformation risk of only 5%. Our findings may facilitate reasonable treatment decisions in elderly patients with CMML.